Power Consumption-Based Server Selection Algorithms for Communication-Based Systems - Enokido, Tomoya; Aikebaier, Ailixier; Takizawa, Makoto; Deen, S Misbah (2010 13th International Conference on Network-Based Information Systems, 2010)
We have to reduce the total electrical power consumption in information systems. In this paper, we consider communication based applications where a server transmits a large volume of data to a client like file transfer protocol (FTP). We discuss a power consumption model for communication-based applications, where the total power consumption of a server depends on the total transmission rate and number of clients where the server concurrently transmits files. A client has to select a server in a set of possible servers, each of which holds a file, so that the power consumption of the server is reduced. We evaluate a pair of PCB (power consumption-based) and TRB (transmission rate-based) algorithms to select a server. In the evaluation, we show the total power consumption can be reduced by the PCB and TRB algorithms compared with the traditional round-robin (RR) algorithm and PCB is more practical than TRB.